Steady, dynamic and creep rheological analysis as a novel approach to detect honey adulteration by fructose and saccharose syrups: Correlations with HPLC-RID results - Yilmaz, Mustafa Tahsin; Tatlisu, Nevruz Berna; Toker, Omer Said; Karaman, Safa; Dertli, Enes; Sagdic, Osman; Arici, Muhammet (ELSEVIER, 2014)
In this study, natural honey was adulterated with the addition of adulterants, namely saccharose and fructose syrups at a ratio of 0%, 10%, 20%, 30%, 40% and 50% by weight. Steady, dynamic and creep tests were conducted, revealing that the changes in the flow, viscoelastic and creep behavior of natural honey were clear and remarkable. Syrup addition decreased viscosity (eta), storage (G') and loss modulus (G '') values of the control honey samples. Deformation represented by the compliance (J(t)) values was more prominent in the adulterated honey samples. In addition, HPLC-RID analysis was conducted to determine major sugar composition of the adulterated samples. Pearson's correlation test indicated that there were significant (P < 0.05; 0.01) correlations between sugar composition and rheology parameters, eta (viscosity), K '', K* (intercepts for G '' and complex modulus (G*), respectively) and eta(o) (viscosity of Maxwell dashpot), suggesting that K', K '', K* and m could be prominent indicators for presence of saccharose or fructose syrups added in natural honey within the studied concentration levels. These results suggested that use of steady, dynamic and creep analysis would be a novel and potential approach to detect honey adulteration by fructose and saccharose syrups. (C) 2014 Published by Elsevier Ltd.
Keywords: Honey; Adulteration; Saccharose and fructose syrups; Rheology; HPLC-RID; CORN SYRUP; BIOACTIVE PROPERTIES; MASS-SPECTROMETRY; REDUCING SUGARS; RATIO ANALYSIS; PLANT SUGARS; CHROMATOGRAPHY; BEHAVIOR; CRYSTALLIZATION; TEMPERATURE; Food Science & Technology